Circadian clock gene expression regulates cancer cell growth through glutaminase - Huang, Aixia; Bao, Bingbo; Gaskins, H Rex; Liu, Haijun; Zhang, Xueli; Lu, Liwen; Gao, Shan; Shi, Yihai; Zhang, Ming; Shan, Yuanzhou; Feng, Jing; Yao, Guoxiang (Acta biochimica et biophysica Sinica, 2014)
Glutamine is an essential amino acid for malignant tumor cells. Glutaminase that metabolizes glutamine reaches a maximum expression in tumors immediately before the maximum proliferation rate. Tumor cells grow at different rates during the day. We postulated that the activity of glutaminase in tumor cells is subject to the regulation of circadian clock gene. We measured glutaminase by western blot analysis and circadian clock gene expression by real-time polymerase chain reaction in the liver and tumor cells at six equispaced time points of the day in individual mice of a 12/12 h light/dark schedule. The results showed that the tumor-bearing mice, under normal diurnal conditions, are circadianly entrained, as reflected by the normal host locomotor activity rhythms and rhythmic liver clock gene expression. The tumors within these mice are also circadianly organized, as reflected by circadian clock gene （Bmall） expression. What is most remarkable is that kidney-type glutaminase also showed circadian rhythms in the same pattern with tumor circadian clock gene expression in liver cancer xenograft model, indicating that conditionally inhibiting glutaminase activity may provide a new target for cancer therapy.